2016
DOI: 10.3892/etm.2016.3624
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-like receptor 4 in lungs of immune-suppressed rat with Acinetobacter baumannii infection

Abstract: Toll-like receptor 4 (TLR4) is involved in the regulation of host responses to Acinetobacter baumannii (A. baumannii). The aim of the present study was to examine the function of TLR4 in lung inflammation in immune-suppressed rats with A. baumannii infection. A total of 72 Sprague-Dawley male rats were randomly divided into the control, A. baumannii infection and immune-suppressed infection groups. The immune-suppressed infection group was treated with 100 mg/kg hydrocortisone by subcutaneous injection every o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[22][23][24] Eventually, this produces a large number of inflammatory cytokines such as IL-6 and TNF-α. 25,26 These results suggested that the TLR4/NF-κB signaling pathway was involved in the process of crush injury induced AKI and promoted the release of inflammatory factors. When added TLR4 inhibitor in the crush groups, kidney function related indicators, such as creatinine, BUN, Mb, and potassium, were significantly improved, and the release of proinflammatory factors were significantly reduced.…”
Section: Discussionmentioning
confidence: 88%
“…[22][23][24] Eventually, this produces a large number of inflammatory cytokines such as IL-6 and TNF-α. 25,26 These results suggested that the TLR4/NF-κB signaling pathway was involved in the process of crush injury induced AKI and promoted the release of inflammatory factors. When added TLR4 inhibitor in the crush groups, kidney function related indicators, such as creatinine, BUN, Mb, and potassium, were significantly improved, and the release of proinflammatory factors were significantly reduced.…”
Section: Discussionmentioning
confidence: 88%
“…Studies using mouse and rat models have confirmed the important role of TLR4 in the host innate defense against respiratory and systemic A. baumannii infection (Knapp et al, 2006 ; Lin et al, 2012 ; Wang et al, 2016 ; Peng et al, 2018 ; Zhang et al, 2018 ). TLR4-/- mice were more susceptible to intranasal A. baumannii infection than wild-type mice (Knapp et al, 2006 ), with higher tissue bacterial burdens and more persistent infection.…”
Section: Host Innate Immune Responses To a Baumanniimentioning
confidence: 93%
“…Recent studies have shown that immunology plays an important role in the occurrence and development of IPF (18). For example, Toll-like receptor 4 (TLR4) is involved in the regeneration and renewal of type II alveolar epithelial cells, affecting the repair of lung injury and the formation of fibrosis (19,20). Macrophage infiltration and high levels of reactive oxygen species (ROS) have been shown to be the key characteristics of lung fibrosis (21).…”
Section: Introductionmentioning
confidence: 99%